Division of labor in society / translated by George Simpson - "Durkheim, Emile" (New York, 1964)
For a quarter of a century, Emile Durkheim dominated French social thought. His influence continues to increase today. This book is the translation of Durkheim?s first great work De la division du travail social. It remains, both from a historical and contextual standpoint, a book that must be read by all who profess some interest in social problems. Durkheim explores a number of engrossing questions, all of them important, all of them provocative: Can it be that progress arises from the boredom that familiar pleasures cause? What does civilization?s rising rate of suicide signify? Does the division of labor within society produce solidarity? Does it weaken the individual personality? What is the nature of class war? A special feature of this book is Durkheim?s long introduction to the original edition. In it he outlined the problem to which he returned in his last years, the source of his crowning work?the science of ethics.
Keywords: Sociology